2021
DOI: 10.12965/jer.2142290.145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of motor impairment on exercise capacity and quality of life in patients with Parkinson disease

Abstract: This study evaluated the impact of motor impairment (MI) on exercise capacity and quality of life in patients with Parkinson disease (PD). One hundred ninety-two patients (≥50 years old) were divided according to the Hoehn and Yahr stages in: mild (stage I), mild to moderate (stage II), moderate (stage III), and advanced MI (stage IV). Exercise capacity (6-min walk test [6MWT]) and quality of life (Parkinson’s Disease Questionnaire [PDQ-39]) were obtained. In this context, 6MWT was progressively worse with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…There was a correlation between age and QoL, especially the dimensions of mobility, daily physical activity, communication, and body discomfort, similar to the findings of Kanegusuku et al [ 29 ], which concluded that both aging and the time since diagnosis of the disease are risk factors for motor impairment in these patients, due to the worsening of domains and, consequently, reduced QoL. Following the same pattern, in the sample observed in the present study, as age advanced, there was a worsening in QoL, regardless of the gender and nutritional status of the participants.…”
Section: Discussionsupporting
confidence: 88%
“…There was a correlation between age and QoL, especially the dimensions of mobility, daily physical activity, communication, and body discomfort, similar to the findings of Kanegusuku et al [ 29 ], which concluded that both aging and the time since diagnosis of the disease are risk factors for motor impairment in these patients, due to the worsening of domains and, consequently, reduced QoL. Following the same pattern, in the sample observed in the present study, as age advanced, there was a worsening in QoL, regardless of the gender and nutritional status of the participants.…”
Section: Discussionsupporting
confidence: 88%
“…The maximum HR percentage in our PD subjects meets a recently defined universal prescription of aerobic exercise for PD populations of 3x/week, 30–40 min, with a 60–80% HR reserve and only a slightly lower HR max than the 70–85% reported by Alberts and Rosenfeldt [ 58 ].We anticipate that the neurobiological mechanisms activated with aerobic exercise at an intensity of 8–10 m/min in a Pink1 rat PD model would also manifest in human PD, given equal exercise duration (∼30–40 min) and frequency (3 sessions per week). Such translation is vital to identify and define the key neurobiological mechanisms engaged by exercise that could alleviate disease progression, particularly as the ability to consistently exercise may decrease with disease severity or encountering barriers to exercise [ 10–14 ]. With this knowledge we can identify the endogenous neurobiological mechanisms engaged by an effective aerobic exercise regimen to reveal the best molecular targets for developing pharmacological or genetic therapies to improve motor or cognitive function, possibly at any stage of PD.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to limited resources available to image the brain with great enough detail to discern the impact exercise may have to increase dopamine signaling [50,51,53]. However, by standardizing parameters of cardiovascular functioning in response to aerobic exercise, rat PD models can play a major role to reveal dopaminergic and other neurobiological mechanisms [54][55][56][57] that may extend to the exercising PD patient, particularly in the context of evaluating the long-term effects of aerobic exercise against the natural progression of PD [10,58].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation